Experimental investigation of underwater laser cutting for thick stainless steel plates using a 6-kW fiber laser. (April 2022) - Oh, Seong Y.; Shin, Jae Sung; Park, Seungkyu; Kwon, Sungok; Nam, Sungmo; Kim, Taeksoo; Park, Hyunmin; Lee, Jonghwan
Highlights: Underwater laser cutting was performed on stainless steel with 50–80 mm thicknesses. The steel blocks were sliced into two pieces using 6 kW fiber laser and dual nozzle. The average kerf widths were measured to be narrower in the range of 1.1–1.2 mm. Experimental results demonstrated that the laser cutting tool can reduce kerf width. Abstract: In this study, underwater cutting using a 6-kW fiber laser was performed to quantitatively investigate the kerf width. The kerf width, material thickness, and cutting speed significantly affect the production rate of debris that would be secondary waste at the decommissioning site. In particular, we cut stainless steel blocks with the thickness of 50, 60, 70, and 80 mm into two pieces to determine the mass loss in the cutting process, which is required for the calculation of the kerf width. The mass loss was determined from the difference in the weight of the steel blocks before and after laser cutting. The average kerf widths and mass loss per cut length (g/m) were calculated using information on the mass loss, laser-cut surface area, steel density, and cut length. The measured kerf widths and mass loss per cut length varied in the range of 1.1–1.2 mm and 475–750 g/m, respectively.